Total fluoride intake in children aged 22-35 months in four Colombian cities (2005)
Abstract –  Objective: To obtain information on the level of total fluoride intake from food, beverages and toothpaste by children at the age of 22–25 months of low and high socioeconomic status (SES) in major Colombian cities. Methods: Daily fluoride intake was assessed by the duplicate plate method and by recovered toothpaste solution during a 3‐day period and afterwards analysed by the microdiffusion method. Results: Mean daily fluoride intake was 0.11 (±0.10), 0.14 (±0.12), 0.10 (±0.07) and 0.07 (±0.06) mg/kg body weight (bw)/day in Bogotá, Medellín, Manizales and Cartagena, respectively. The total fluoride intake was higher in low‐SES subjects in the cities of Medellín and Bogotá. In the high‐SES children of the four cities, the average intakes ranged from 0.06 to 0.09 mg F/kg bw, whereas, the low‐SES children in three cities had intakes between 0.11 and 0.21 mg F/kg bw (Cartagena, 0.07). Toothpaste (containing 1000–1500 ppm F, with 1500 ppm F being more common) accounted for approximately 70% of total fluoride intake, followed by food (24%) and beverages (<6%). More than half the children had their teeth brushed by an adult, on average twice a day, using 0.22–0.65 g of toothpaste. Conclusion: Children from three Colombian cities have a mean total daily fluoride intake above the ‘optimal range’. Health authorities should promote an appropriate use of fluoridated dentifrices discouraging the use of dentifrices containing 1500 ppm F in children younger than 6 years of age and promoting a campaign of education of parents and oral health professionals on adequate toothbrushing practices.